Search for supersymmetry in final states with a single lepton, $b$-quark jets, and missing transverse energy in proton-proton collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2198 authors) (2013)
A search motivated by supersymmetric models with light top squarks is presented using proton-proton collision data recorded with the CMS detector at a center-of-mass energy of sqrt(s) = 7 TeV during 2011, corresponding to an integrated luminosity of 4.98 inverse femtobarns. The analysis is based on final states with a single lepton, b-quark jets, and missing transverse energy. Standard model yields are predicted from data using two different approaches. The observed event numbers are found to be compatible with these predictions. Results are interpreted in the context of the constrained minimal supersymmetric standard model and of a simplified model with four top quarks in the final state.